Observer-based iterative learning control design in the repetitive process setting*. Issue 1 (July 2017) - Paszke, Wojciech; Rogers, Eric; Patan, Krzysztof
Abstract: This paper considers the design of an observer-based iterative learning control law for discrete linear systems using repetitive process stability theory The resulting design produces a stabilizing feedback controller in the time domain and a PD-type of feedforward controller that guarantees monotonic convergence in the trial-to-trial domain. Furthermore, the new design procedure includes limited frequency range specifications, which will be of particular interest in some applications. All design computations required for the new results in this paper can be completed using linear matrix inequalities. A simulation example is given to illustrate the theoretical developments.